Novel mitophagy inducer TJ0113 alleviates pulmonary inflammation during acute lung injury - Liu, Zhengyuan; Fang, Danruo; Chen, Kaijun; Dong, Lingling; Huang, Huaqiong; Chen, Zhihua (Frontiers in Pharmacology, 2025)
IntroductionAcute lung injury (ALI) is a severe respiratory disease with limited effective therapeutic options. Recent studies have highlighted mitochondrial damage as a crucial factor in the progression of ALI. Mitophagy, which facilitates the removal of damaged mitochondria, has been shown to reduce inflammation. Our collaborators constructed a small molecule mitophagy inducer, TJ0113. TJ0113 has been approved to initiate a Phase I clinical trial for Alport syndrome and a Phase II trial for Parkinson's disease in China. Therefore, we explored the potential of TJ0113 as a novel therapeutic for ALI.MethodsThe mitophagy-inducing potential of TJ0113 was assessed in HEK293T cells. The anti-inflammatory effects of TJ0113 were further evaluated in vivo using a mouse model of lipopolysaccharide (LPS)-induced ALI and in vitro using LPS-stimulated bone-marrow-derived macrophages (BMDMs).ResultsTJ0113 selectively induced mitophagy in damaged mitochondria. Furthermore, the PINK1–Parkin pathway was identified as a specific mitophagy pathway induced by TJ0113. In LPS-induced ALI mouse model, intraperitoneal injection of TJ0113 significantly reduced lung inflammation and mortality. In vitro, TJ0113 significantly inhibited the expression of LPS-induced inflammatory cytokines in BMDMs. Finally, we found that TJ0113 inhibited LPS-induced inflammation by inducing mitophagy and inhibiting nuclear factor κB (NF-κB) and inflammasome activation.ConclusionTJ0113 alleviates LPS-induced inflammation by inducing mitophagy and inhibiting NF-κB and inflammasome activation. Its selective action on damaged mitochondria suggests minimal side effects, positioning TJ0113 as a promising therapeutic candidate for ALI.